Optimasi Proses Pembuatan Arang Batang Sawit Melalui Proses Karbonisasi Menggunakan Response Surface Methodology - Mia Afriyenti; Zuchra Helwani; Warman Fatra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Palm oil trunk until this date is a waste which still not been used maximally, so palm oil trunk have potential to be used as alternative energy resource of solid fuel with the way of increasing its calorific value through carbonization process. Carbonization is converting process of biomass to become charcoal at temperature range 300-600 oC in inert condition. The objective of this research is to study the characteristics of resulted solid fuels. Palm oil carbonization used tube furnace as reactor within operating conditions of temperature (350, 400 and 450 oC), residence time (90, 120 and 150 minutes) and feed size (2, 4 and 6 cm). The analized responses were calorific value and volatile matter content. Obtained result for calorific value amounts 24,426.300-28,929.100 kJ/kg and volatile matter content amounts 8-19 %. The obtained analysis is processed using Design Expert v7.0.0 Trial Version. Processing data begins with using first order to see the degree of curvature. Degree of curvature obtained indicate the model to use is second order. Level of significance between variables can be observed from the value of P-value < 0,05 and lack of fit > 0,05, which indicate that model is suitable with the obtained data. R2 obtained for Y1 = 0.9486 and Y2 = 0.9704. The most influential factors to all responses are carbonization temperature followed with residence time and feed size. At optimum operating conditions (temperature 449,99 °C during 149,96 minutes with feed size 2 cm), the value of optimum responses obtained are Y1= 28.282,2 kJ/kg and Y2 = 9,234 %.Keywords : biomass, carbonization, optimization, palm oil trunk, rsm, solid fuel